(untitled) (Ukrainian Journal of Ophthalmology, 2026)
After a serious and extended disease, Lyudmila T. Kashintseva, MD, Professor, an ophthalmic surgeon and scientist, died on May 12, 2016. Her name is known in Ukraine and abroad, she was a member of European Glaucoma Society. She is an author of more than 300 scientific papers including two monographs, Basis of Ophthalmic Endocrinology (1977) and Ophthalmogeriatrics (1982) which have become the bible for ophthalmologists. She was a thesis advisor for 10 Candidates and 3 Doctors of Science (Medicine) in research areas headed by her. Lyudmila Kashintseva founded a young scientists’ school and educated a great number of researchers and clinicians specialized in glaucoma and ophthalmoendocrinology.